The deubiquitinating enzyme DUBAI stabilizes DIAP1 to suppress Drosophila apoptosis. - Yang, C.S.; Sinenko, S.A.; Thomenius, M.J.; Robeson, A.C.; Freel, C.D.; Horn, S.R.; Kornbluth, S. (Cell Death and Differentiation, 2014)
Deubiquitinating enzymes (DUBs) counteract ubiquitin ligases to modulate the ubiquitination and stability of target signaling molecules. In Drosophila, the ubiquitin-proteasome system has a key role in the regulation of apoptosis, most notably, by controlling the abundance of the central apoptotic regulator DIAP1. Although the mechanism underlying DIAP1 ubiquitination has been extensively studied, the precise role of DUB(s) in controlling DIAP1 activity has not been fully investigated. Here we report the identification of a DIAP1-directed DUB using two complementary approaches. First, a panel of putative Drosophila DUBs was expressed in S2 cells to determine whether DIAP1 could be stabilized, despite treatment with death-inducing stimuli that would induce DIAP1 degradation. In addition, RNAi fly lines were used to detect modifiers of DIAP1 antagonist-induced cell death in the developing eye. Together, these approaches identified a previously uncharacterized protein encoded by CG8830, which we named DeUBiquitinating-Apoptotic-Inhibitor (DUBAI), as a novel DUB capable of preserving DIAP1 to dampen Drosophila apoptosis. DUBAI interacts with DIAP1 in S2 cells, and the putative active site of its DUB domain (C367) is required to rescue DIAP1 levels following apoptotic stimuli. DUBAI, therefore, represents a novel locus of apoptotic regulation in Drosophila, antagonizing cell death signals that would otherwise result in DIAP1 degradation.